A high school replication of targeted professional development for classroom management - Freeman, Jennifer; Kowitt, Jennifer; Simonsen, Brandi; Wei, Yan; Dooley, Kate; Gordon, Lola; Maddock, Eleanor (Remedial and Special Education, 2018)
In areas of emerging research, such as supporting teachers' classroom management, replication of research is critical to ensuring that recommendations for the field are based on sound science and appropriate for the contexts to which they are being applied. This article describes a replication of research on efficient professional development supports for teachers' classroom managements in a new context: high school classrooms. Data did not support a functional relation between teachers' use of specific praise and the targeted professional development and self-management in the high school setting. Results of this study highlight the critical importance of replication in education research. Based on our findings and our experience conducting this study, we suggest several possible adaptations may be necessary for successful replication at the high school level.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-228-318-057-658, pop00145 tex.type: [object Object]
Keywords: behavior; dept.rdg; dept.sed; inservice training; management; peer-reviewed; personnel preparation; research methodology; secondary; single-subject; staff development/inservice

Coteaching in content area classrooms: Lessons and guiding questions for administrators - Sinclair, Anne C.; Bray, Laura E.; Wei, Yan; Clancy, Erin E.; Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J. (NASSP Bulletin, 2018)
Secondary school administrators increasingly include students with disabilities in general education classrooms with coteaching models. Theoretically, coteaching enables two educators to attend to the learning needs of students with disabilities while exposing them to grade-level content area instruction. However, our study on teachers’ perceptions of coteaching found that teachers often viewed their schools’ leadership decisions as adversely affecting their ability coteach effectively. The purpose of this article is to provide administrators with an overview of common coteaching models, summarize findings from our study on teachers’ perceptions of how their schools’ leadership influenced their coteaching practices, and provide a set of guiding questions to consider when seeking to support coteaching. © 2018 SAGE Publications.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-514-925-194-03X, pop00123 tex.type: [object Object]
Keywords: coteaching; dept.rdg; dept.sed; inclusion; instructional leadership; peer-reviewed; professional development

Higher education and disability: A systematic review of assessment instruments designed for students, faculty, and staff - Lombardi, Allison; Gelbar, Nicholas; Dukes, III, Lyman L.; Kowitt, Jennifer; Wei, Yan; Madaus, Joseph; Lalor, Adam R.; Faggella-Luby, Michael (Journal of Diversity in Higher Education, 2018)
In this study, the literature in disability and higher education was examined, with a specific focus on assessment instruments. Published articles (n = 203) on development of new or refinement of existing instruments were reviewed for traits measured and psychometric rigor reported. Findings showed instruments are intended for professionals and students, and of the student instruments, broad categories are academic, nonacademic, and specific to a disability diagnosis. Not all instruments are limited to students with disabilities; many of the reviewed instruments can be utilized in higher-education settings on all students, faculty, and staff, regardless of disability. The implications of the findings undergird the urgency to prioritize disability as a facet of diversity within higher-education scholarship, and furthermore aid this prioritization by providing a catalogue of robust instruments to researchers and practitioners.
25 citations (Crossref) [2023-10-31] tex.eissn: 1938-8934 tex.unique-id: ISI:000426973700003
Keywords: Disability; assessment; campus climate; dept.rdg; dept.sed; peer-reviewed; program evaluation

Reading comprehension and co-teaching practices in middle school English language arts classrooms - Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J.; Mitchell, Marisa; Clancy, Erin; Davidson, Kimberly A.; Sinclair, Anne C.; Wei, Yan (Exceptional Children, 2018)
This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally, we report the types of text used. Observations revealed that more than half of time spent on literacy activities involved reading aloud or silently with no co-occurring literacy instruction that supports reading comprehension. Students with disabilities spent a majority of their time in whole-class instruction or working independently with little teacher interaction. Special education teachers spent most of their time supporting whole-class instruction led by the content-area teacher. Implications and directions for future research are provided.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-264-196-907-683, pop00086 tex.type: [object Object]
Keywords: dept.rdg; dept.sed; peer-reviewed